Defining Indigenous in Indonesia and Its Applicability to the International Legal Framework on Indigenous People’s Rights - Fahmi, Chairul; Jihad, Azka Amalia; Matsuno, Akihisa; Fauzan, Faisal; Stoll, Peter-Tobias (Universitas Negeri Semarang, 2023)
This paper aims to analyse the concept of indigenous peoples in Indonesia and examines whether the concept is appropriate with an international legal framework. Analysing the concept is essential to legitimising indigenous rights under the international law regime. The discourse on indigenous in Indonesia emerged after the government rejected an international treaty on indigenous rights and was reluctant to adopt the UNDRIP into their national law. The government opposes this by arguing that the concept of indigenous peoples under the international legal framework is inappropriate for the Indonesian context. Consequently, indigenous peoples in Indonesia do not benefit from international norms that have recognised and protected their rights globally. This paper found that the concept of indigenous peoples in Indonesia has similarities and is appropriate to the international instrument (ILO169 and UNDRIP). Thus, ratifying the ILO treaty or adopting the UNDRIP into national law will benefit the indigenous in protecting their fundamental rights, including their collective rights to traditional lands under international norms.